Relationship Between Conceptual Metaphors And Arabicroots in the Qur'an - Sardaraz, Khan; Roslan, Ali (2018)
Previous literature investigated various conceptual metaphor themes in the Quran, but it did not linguistically analyze the relationship between the Arabic roots and conceptual metaphor. This paper has applied lexical concept and cognitive model theory (LCCM) to linguistically analyze the relationship between the Arabic roots and the conceptual metaphors. Data has been extracted through the technique of topical words and phrases, and metaphor identification procedure (MIP) has been employed for metaphors identification in the themes of rewards and punishments in the Quran. The analysis of 129 linguistic instantiations of 33 conceptual metaphors in three major source domains shows that the roots in the Arabic language are equivalent to primary cognitive models in LCCM theory. Conceptual metaphors reside at the level of roots or primary cognitive models in the most metaphoric expressions because lexical items directly access the primary cognitive model for semantic argument. However, the findings also deviate from the LCCM theory, and show that conceptual metaphors do not map the primary cognitive models in metonymic linguistic expressions and novel metaphors, but rather, they are identified after a thorough linguistic analysis. It shows that the semantic distance between source and target domain in conventional metaphors is less than the semantic distance in novel metaphors and metonymies. This paper recommends further studies on the relationship between the Arabic roots and the conceptual metaphor for drawing more cognitive semantic insights in metaphoric expressions.